Pengaruh Performance Expectancy dan Effort Expectancy Terhadap Continuance Intention to Use Melalui Mediasi Attitude Towards Use pada Aplikasi Netflix - Nur Alfianti; Andi Muhammad Sadat; Daru Putri Kusumaningtyas (Teewan Journal Solutions, 2026)
This study aims to examine the influence of Performance Expectancy and Effort Expectancy on Continuance Intention to Use Through Attitude Towards Use Mediation on the Netflix Application. The population in this study are individuals belonging to Generation Z (Gen Z) who live in the Greater Jakarta area and are active users of the Netflix digital streaming application. Gen Z or Generation Z used in Indonesia began from 1997 to 2012 based on official data set by the Indonesian Central Statistics Agency (BPS). The recommended sample size for this study is around 400 respondents to ensure that the research results can represent the population with an adequate level of confidence. This study uses Structural Equation Modeling (SEM) data analysis techniques with the Partial Least Square (PLS) approach, which is analyzed using SmartPLS software version 4. The results of the study found that Performance Expectancy (PE) has a positive and significant influence on Continuance Intention to Use (CITU). Effort Expectancy (EE) has a positive and significant influence on Continuance Intention to Use (CITU). Attitude Towards Use (ATU) has a positive and significant effect on Continuance Intention to Use (CITU). Performance Expectancy (PE) has a positive and significant effect on Attitude Towards Use (ATU). Effort Expectancy (EE) has a positive and significant effect on Attitude Towards Use (ATU). Performance Expectancy (PE) has a significant indirect effect on Continuance Intention to Use (CITU) through Attitude Towards Use (ATU). Effort Expectancy (EE) has a significant indirect effect on Continuance Intention to Use (CITU) through Attitude Towards Use (ATU).